2018
DOI: 10.1016/j.learninstruc.2017.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Variation in situation-specific engagement among lower secondary school students

Abstract: The majority of previous research has examined school engagement as an overall student characteristic. The present study contributes to the field by examining variation in students' situation-specific engagement from one lesson to another and by investigating situational determinants of such variation. An intensive one-week lesson-to-lesson data collection was conducted in four lower secondary school classrooms. Students rated their situation-specific engagement at the end of each lesson with a mobile-based In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 44 publications
(96 reference statements)
3
31
0
2
Order By: Relevance
“…The present study examined the relation between the of teacher–student interactions in lower secondary school, which were assessed using a widely used observational instrument, CLASS‐S, and students’ self‐ratings of situational engagement at the end of the same lessons. The relevance of this line of research can be justified based on the notion of malleability and situational variability of student engagement (Martin et al ., ; Pöysä et al ., ; Vasalampi et al ., ). Because students’ engagement can fluctuate from one lesson to another, each lesson is also a new opportunity for students to become engaged in learning and for teachers to support such engagement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study examined the relation between the of teacher–student interactions in lower secondary school, which were assessed using a widely used observational instrument, CLASS‐S, and students’ self‐ratings of situational engagement at the end of the same lessons. The relevance of this line of research can be justified based on the notion of malleability and situational variability of student engagement (Martin et al ., ; Pöysä et al ., ; Vasalampi et al ., ). Because students’ engagement can fluctuate from one lesson to another, each lesson is also a new opportunity for students to become engaged in learning and for teachers to support such engagement.…”
Section: Discussionmentioning
confidence: 99%
“…According to Fredricks et al . (), engagement is presumed to be malleable, and recent research has indicated that student engagement varies situationally from one learning situation to another (e.g., Martin et al ., ; Pöysä et al ., ; Shernoff et al ., ; Vasalampi et al ., ). Thus, in everyday learning at school, this fluctuating engagement can be shaped by factors such as structural features of the classroom and factors related to the interactions between teachers and students (Fredricks et al ., ).…”
Section: Introductionmentioning
confidence: 98%
“…The focus of these debates is primarily on upper secondary and tertiary education. However, there are also concerns about disengagement and alienation from school at lower levels (Pöysä et al, 2018). Policies directed at pupils in lower secondary education often include pre-vocational education.…”
Section: Pre-vocational Education and The Lower Secondary School Currmentioning
confidence: 99%
“…Grieco, Jowers and Bartholomew, 2009;Jarrett et al, 1998), at the class level (e.g. Pöysä et al, 2017;Barros, Silver and Stein, 2009), or reported on by teachers (e.g. Carlson et al, 2015;Barros et al, 2009) or parents (e.g.…”
Section: Introductionmentioning
confidence: 99%